2013
DOI: 10.1038/aps.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

NVP-BEZ235, a novel dual PI3K/mTOR inhibitor, enhances the radiosensitivity of human glioma stem cells in vitro

Abstract: Aim: NVP-BEZ235 is a novel dual PI3K/mTOR inhibitor and shows dramatic effects on gliomas. The aim of this study was to investigate the effects of NVP-BEZ235 on the radiosensitivity and autophagy of glioma stem cells (GSCs) in vitro. Methods: Human GSCs (SU-2) were tested. The cell viability and survival from ionizing radiation (IR) were evaluated using MTT and clonogenic survival assay, respectively. Immunofluorescence assays were used to identify the formation of autophagosomes. The apoptotic cells were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…AZD2014 is an inhibitor of mTOR and has been shown to enhance radiation sensitivity, apoptosis, and DNA damage, and to suppress proliferation and clonogenicity [30, 31]. For example, this inhibitor of the mTOR pathway enhanced the radiosensitivity of prostate cancer and glioma stem cells [32, 33]. Consistent with the role of mTOR observed in previous studies, we found that AZD2014 enhanced cellular sensitivity to radiation; by contrast, upregulating mTOR expression decreased radiation sensitivity.…”
Section: Discussionsupporting
confidence: 88%
“…AZD2014 is an inhibitor of mTOR and has been shown to enhance radiation sensitivity, apoptosis, and DNA damage, and to suppress proliferation and clonogenicity [30, 31]. For example, this inhibitor of the mTOR pathway enhanced the radiosensitivity of prostate cancer and glioma stem cells [32, 33]. Consistent with the role of mTOR observed in previous studies, we found that AZD2014 enhanced cellular sensitivity to radiation; by contrast, upregulating mTOR expression decreased radiation sensitivity.…”
Section: Discussionsupporting
confidence: 88%
“…3A). P7170 treatment induced G 1 -S cell-cycle arrest with an increase in G 1 population from 52.3% (DMSO controls) to 65.9% (30 nmol/L P7170-treated cells) and sub-G 1 population increased from 1.1% to 63.3% (1,000 nmol/L P7170-treated cells), an observation consistent with the growth arrest and cell death expected with PI3K/AKT/ mTOR signal inhibition (27). This considerable increase in the sub-G 1 population observed following P7170 treatment was dose-and time dependent (Fig.…”
Section: P7170 Exhibits Antiproliferative Activity Toward Various Cansupporting
confidence: 73%
“…The autophagic process during G 1 arrest can repair cell damage to avoid cell death [28] . Some inhibitors of the AKT signaling pathway, such as NVP-BEZ235, induce tumor cell autophagy and cell cycle arrest [29] . Our results demonstrated that fucoxanthin induced cell cycle arrest at the G 0 /G 1 phase via inhibiting the AKT signaling pathway and that fucoxanthin also regulated the expression of cell cycle-related proteins by upregulating p21 expression and downregulating CDK2 and cyclin D1 expression.…”
Section: Discussionmentioning
confidence: 99%